2020
DOI: 10.31224/osf.io/wdztv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lightning for Energy and Material Uses: A Structured Review

Abstract: The average atmospheric charge density of Earth is neutral. Charge built up from thunderstorms and lightning phenomena is offset by oceanic surface charging, and offers a source of energy that has not been harnessed broadly. Unfortunately, the total terrestrial energy of the Earth’s atmospheric electrical system is modest (250–500 MW) compared to industrial requirements: Innovations are likely to offer improvements to societal efficiency rather than broad transformations. Direct capture systems located in plac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Devices like horns and arresters for transmission lines that aid open and stop circuits in the event of an overvoltage are examples of infrastructure protection against lightning [14]. Sources of lightning provide more electricity than other types of energy.…”
Section: Electricity Tapped By Lightning Arrestermentioning
confidence: 99%
See 1 more Smart Citation
“…Devices like horns and arresters for transmission lines that aid open and stop circuits in the event of an overvoltage are examples of infrastructure protection against lightning [14]. Sources of lightning provide more electricity than other types of energy.…”
Section: Electricity Tapped By Lightning Arrestermentioning
confidence: 99%
“…Energy harvesting as a field looks at modest amounts of energy stored for low energy applications, for example, in wearable electronics. Three of the five authors found in this category are coauthors on a single paper related to alternating current (AC) energy capture in systems with mechanical or radiofrequency (RF) transducers [14].…”
Section: Harvesting Lightning Energymentioning
confidence: 99%